Lohmannella (Acari, Halacaridae) from a cold-water coral reef off Norway, description of two new and a list of North Atlantic species - Bartsch, Ilse (Zootaxa, 2020)
Cold water coral reefs proved to harbour a diverse halacarid fauna. The fauna extracted from small pieces of corals was dominated by the genus Lohmannella which was represented by three species. Two species, new to science, are described and illustrated, namely Lohmannella njoerdri and Lohmannella sulensis. Of the third species only a single juvenile stage is available, since a reliable identification is not possible. Lohmannella njoerdri is characterized by long, slender claws. Lohmannella sulensis differs from other Lohmannella species by its wide dorsal plates, long and slender gnathosoma and legs and the part of the idiosoma posterior to insertion of leg IV being short.